國民小學多元文化族群學生學習困境脈絡下教師韌性與幸福感之研究 - 張志瑋(Chih-Wei Chang) (Shizi Peiyu Yu Jiaoshi Zhuanye Fazhan Qikan, 2025)
This study explores the causes of learning difficulties in and coping strategies of students from multicultural ethnic groups at national primary schools, as well as the current situation of and relationship between teachers' resilience and well-being in this context. Thirteen teachers from six schools in New Taipei City and Taoyuan City were selected. The results showed that 1. in the context of learning difficulties faced by students from multicultural ethnic backgrounds, teachers' resilience includes positive emotion management, strong interpersonal relationships, situational and resource support, professional growth, job satisfaction, and effective parent-teacher communication; 2. strategies for enhancing teachers' well-being include leveraging successful experiences, fostering teamwork and support, strengthening professional identity and development, cultivating positive traits and a sense of mission, and engaging in continuous self-reflection and growth; and 3. improving teachers' resilience can enhance